Counting states: A combinatorial analysis of SQM fragmentation. Issue 1 (18th December 2022) - Bernardo, Antonio L. C.; Paulucci, Laura; de Sá, Lucas M.; Horvath, Jorge E.
Abstract: The Strange Quark Matter (SQM) hypothesis states that at extreme pressure and density conditions, a new ground state of matter would arise, in which half of the down quarks become strange quarks. If true, it would mean that at least the core of neutron stars is made of SQM. In this hypothesis, SQM would be released in the interstellar medium when two of these objects merge. It is estimated that 10 − 2 M ⊙ $$ {10}^{-2}{M}_{\odot } $$ of SQM would be released this way. This matter will undergo a sequence of processes that should result in a fraction of the released SQM becoming heavy nuclei through the r‐process . In this work, we are interested in characterizing the fragmentation of SQM, with the novelty of keeping track of the quark configuration of the fragmented matter. This is accomplished by developing a methodology to estimate the energy of each fragment as the sum of its constituent quarks, the Coulomb interaction among the quarks and fragments' momenta.